INNAVATCON ROUTES FOR PRODUCING FURANO-EPOXY INDER (Scientific journal of the Fergana State University, 2024)
The influencing factors on the formation of difurfurylidene acetone in the condensation reaction of furfural with acetone and monofurfurylidene acetone with furfural were studied. The mechanism of formation of difurfurylidene acetone was clarified, which made it possible to develop an innovative technological process for the production of furan-epoxy binders.